Struktur Pengendalian Intern dan Efisiensi Penyaluran Kredit pada Lembaga Perkreditan Desa (LPD) - Ariani, Kadek Novi; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 32 No 8 (2022), 2022)
The research has the aim of carrying out empirical evidence of the influence of the internal control structure on the efficiency of lending in South Badung LPD. The data used is primary data, namely questionnaire answers and secondary data, namely LPD Non-Performing Loan (NPL) data. The sample used is 23 LPD in South Badung. Samples were taken by non-probability sampling method, saturated sampling technique. The analytical technique applied is multiple linear regression. The findings show that the control environment, risk assessment, control activities, information and communication, and monitoring have a positive influence on the efficiency of credit distribution. This means that a well-implemented internal control structure can increase the efficiency of lending. Keywords: SPI; Efficiency Of Lending; LPD